2002
DOI: 10.1016/s1534-5807(02)00222-8
|View full text |Cite
|
Sign up to set email alerts
|

Coilin Methylation Regulates Nuclear Body Formation

Abstract: functional homolog, yeast Rmt1/Hmt1, encoding the bulk of the activity (Tang et al., 2000; McBride et al., Center for Human Genetics and Program in Cell Biology 2000). The only type II PRMT defined to date is the Janus kinase binding protein, JBP1/PRMT5 (Branscombe et Case Western Reserve University and University Hospitals of Cleveland al., 2001). There are only five known targets of PRMT5: myelin Cleveland, Ohio 44106 basic protein (Baldwin and Carnegie, 1971) and the spliceosomal proteins SmB/BЈ, SmD1, SmD3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
189
0
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 161 publications
(210 citation statements)
references
References 32 publications
18
189
0
3
Order By: Relevance
“…Therefore, purified Sm proteins from HeLa snRNPs (Raker et al 1996;Sumpter et al 1992) were used as a known source of sDMA-modified binding substrates. GST-pull-down assays demonstrated that SmB/B′, SmD3, and SmD1 were detected by monoclonal antibody Y12, which recognizes sDMA-modified substrates (Brahms et al 2001;Hebert et al 2002). We found that Sm proteins bound to the GST-coilin subfragment, but not to GST alone (Fig.…”
Section: Coilin Interacts With Sm Proteins Irrespective Of Their Metmentioning
confidence: 73%
See 4 more Smart Citations
“…Therefore, purified Sm proteins from HeLa snRNPs (Raker et al 1996;Sumpter et al 1992) were used as a known source of sDMA-modified binding substrates. GST-pull-down assays demonstrated that SmB/B′, SmD3, and SmD1 were detected by monoclonal antibody Y12, which recognizes sDMA-modified substrates (Brahms et al 2001;Hebert et al 2002). We found that Sm proteins bound to the GST-coilin subfragment, but not to GST alone (Fig.…”
Section: Coilin Interacts With Sm Proteins Irrespective Of Their Metmentioning
confidence: 73%
“…Symmetric dimethylarginine (sDMA) modification strongly increases the affinity of SMN for RG dipeptide repeats (Brahms et al 2001;Friesen et al 2001). Consistent with these observations, coilin hypomethylation results in delocalization of SMN to twin structures called Gemini of CBs, or gems (Boisvert et al 2002;Hebert et al 2002). In addition to SMN, coilin's direct binding partners include itself (Hebert and Matera 2000), the nucleolar protein Nopp140 (Isaac et al 1998) and SmB/B′ (Hebert et al 2001).…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations